(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
The internet is a global network made up of millions of private, public, academic, business, and government networks connected by electrical, wireless, and optical technologies. Internet technology refers to the wide range of protocols and technologies that make the internet easier to use and function. The aim of the study is to evaluate how the internet has affected Nigerian Journalism practice while highlighting the underutilisation of modern communication technologies in the country’s journalism industry. This study adopted two theories which are technological determinism theory and democratic participant theory. The conclusion of the study is that people use the internet to search for information and updates on current events, which has forced journalists to look for every way to expand on their coverage of many topics. Unlike print publications which have a limited number of pages, the audience may access more news on the internet in a timely manner and watch it through a sequence of images and video snippets that add to the news vibrancy. This study recommends that media organisations should train their employees through workshops so as to be knowledgeable about anything related to the internet. Also, government should allocate funds for the construction of infrastructure in remote areas to enable journalists send and receive reports more quickly and easily.